1978
DOI: 10.1002/chin.197845273
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: PHENOPHOSPHAZINES. IV. ELECTRONIC EFFECTS IN 5‐METHYL‐10‐OXO‐5,10‐DIHYDROPHENOPHOSPHAZINES

Abstract: Das cyclische Phosphinsäurechlorid (I) reagiert mit der Grignardverbindung (II) zur Verbindung (III), aus der mit Aluminiumchlorid das Phenol (IV) entsteht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They also found that the reaction of 3 and the Schiff base PhCH=NPh yields the adduct earlier described by Messinger.14 When the oxide 3 is dissolved in THF and treated first with NaH and then with Mel, both the phosphorus and nitrogen atoms are methylated. 44,46 The interaction Me 33a of 3 and Ar,N,Ar/,Ar,-tetraethylmethanediamine in boiling EtOH also yields a tertiary phosphine oxide. 67 Treatment of this oxide with picric acid gives a 1:1 adduct.…”
Section: Addition To Unsaturated Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also found that the reaction of 3 and the Schiff base PhCH=NPh yields the adduct earlier described by Messinger.14 When the oxide 3 is dissolved in THF and treated first with NaH and then with Mel, both the phosphorus and nitrogen atoms are methylated. 44,46 The interaction Me 33a of 3 and Ar,N,Ar/,Ar,-tetraethylmethanediamine in boiling EtOH also yields a tertiary phosphine oxide. 67 Treatment of this oxide with picric acid gives a 1:1 adduct.…”
Section: Addition To Unsaturated Compoundsmentioning
confidence: 99%
“…The dinitration of the tertiary phosphine oxide 33a has also been accomplished by the use of HN03 in acetic acid. 46 Although the structure of the product was not proven, it was reasonably assumed that the nitro Sergeev and Kudryashov2 were the first to report the synthesis of esters of the phosphinic acid 30. They converted the acid to the silver salt and then allowed the latter compound to react with Mel or EtI.…”
Section: + Et2nch2net2mentioning
confidence: 99%
See 1 more Smart Citation